The Authority of Notaries & Land Deed Making Officials (PPAT) from The Perspective of The Code of Ethics: Overlaps & Their Legal Implications - Suprianto, Mutiara Anggia Putri; Damayanti, Nandaini Intan; Samosir, Tetti (JURNAL AKTA, 2025)
This study discusses the authority of notaries and Land Deed Officials (PPAT) from the perspective of the professional code of ethics, focusing on the phenomenon of overlapping authority and its legal implications. Although the authority of these two positions has been strictly regulated in laws and regulations, in practice there are still frequent deviations, especially by officials who hold two positions at once. This study uses a normative legal approach with a literature study method on laws and regulations, codes of ethics, and related legal documents. The results of the study indicate that the form of overlapping authority occurs when a notary uses his capacity to exercise the authority of a PPAT or vice versa, which results in administrative errors and can harm the parties in legal transactions. The legal implications include the potential for formal defects in the deed, violations of the professional code of ethics, administrative to criminal sanctions, and civil lawsuits by the injured party. Therefore, a deep understanding and discipline are needed in carrying out the functions of each position in accordance with legal provisions and professional ethics to maintain integrity and legal certainty in public services.